Knowledge, attitudes and practices related to HIV/AIDS among learners in Vhembe district of Limpopo Province - M. Davhana-Maselesele; L.L. Lalendle; U. Useh (AOSIS, 2007)
The purpose of this study is to investigate the knowledge, attitudes and practices related to HIV and AIDS among teenagers in rural schools in Vhembe district. This study focused on teenagers' sources of knowledge about HIV/AIDS; their knowledge of how to avoid contracting HIV/AIDS; their knowledge of the methods of transmission of the disease; their knowledge of condoms and usage levels; and people with whom they are comfortable to talk about HIV/AIDS. This was a quantitative descriptive research design where a random sample of 128 participants between the ages of 14 and 19 years was selected. The participants were in grades 8 to 12. The study recommended that holistic HIV/AIDS preventive programmes which were culture and gender sensitive be developed. Custodians of culture should be involved in dealing with HIV/AIDS. Parents should also play their role in discussing HIV/AIDS with their children in a non-threatening environment.